Analisis Pasal 80 Ayat (4) Kompilasi Hukum Islam terhadap Peran Istri sebagai Pencari Nafkah Utama di Kecamatan Tanjung Tiram, Kabupaten Batu Bara - Aunur Rofiq Muhammad Adli; Khairani Khairani; Boihaqi bin Adnan (AHKAM, 2025)
Marriage in Islam positions the husband as the party obligated to provide maintenance for his wife and children, as stipulated in Article 80(4) of the Kompilasi Hukum Islam (KHI). However, the social dynamics of modern society show a shift in household roles, in which, under certain conditions, the wife becomes the primary breadwinner. This study aimed to analyze the role of the wife as the main breadwinner within household structures in Tanjung Tiram Subdistrict, Batu Bara Regency, and to examine this phenomenon from the perspective of Article 80(4) of the KHI. A descriptive qualitative approach with a juridical-sociological method was employed, with data obtained through interviews with five wives who act as primary breadwinners and analyzed using descriptive-qualitative techniques. The findings indicate that the wife’s role as the main breadwinner is driven by the husband’s inability to fulfill his maintenance obligations due to illness, unemployment, or age-related factors, so that the wife not only supports the family economy but also continues to carry domestic responsibilities and maintain household harmony. From the perspective of Article 80(4) of the KHI, the obligation of maintenance remains vested in the husband, but its implementation is based on the principle of capability; thus, the wife’s role as the primary breadwinner can be understood as a form of ta‘āwun (mutual assistance) and social adaptation under emergency conditions that is consistent with the principles of justice and family welfare in Islamic law.